Reporting of non-communicable disease research in low- and middle-income countries: a pilot bibliometric analysis - Hofman, Karen (Medical Library Association, 2006)
Objective: The paper identifies the relative amount of research devoted to non-communicable disease in low- and middle-income countries (LMICs). Design: A bibliometric analysis of a subset of journals published in LMICs was performed. Measurements: Seventy-six peer-reviewed journals focused on general medicine or public health published in 46 LMICs and indexed from 1998 to 2003 in MEDLINE. A total of 24 journals were selected, 4 journals from each of 6 LMIC regions. Searches were refined using 18 non-communicable disease topics with 7,012 articles identified for analysis. Results: More than 40% of articles in LMIC regions focused on non-communicable disease research. The percentage was highest in Eastern Europe/Central Asia (47%) and lowest in Latin America (36%). The percentage of articles published in Sub-Saharan Africa (38%) did not differ significantly from that of Latin America or South Asia. Cardiovascular disease and cancer led the list of the top ten most-indexed published topics by region. Conclusions: Even in regions rampant with infectious diseases, some capability exists to conduct research on non-communicable diseases. Greater attention should be paid to the conduct and support of such research in LMICs, which will benefit these countries and may yield clues to lower-cost solutions to the burden of these diseases worldwide.